Pelindungan Hak Pekerja Perempuan dalam Perspektif Feminisme - Susiana, Sali (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2017)
The rights of women workers have been guaranteed in the constitution, several laws, and some of its implementing regulations. In the constitution, the equal rights of women to work and receive appropriate treatment are provided in Article 27 and Article 33. Some of the laws and regulations governing the rights of women workers, among others, are Law Number 13 of 2003 on Manpower, Law Number 8 of 1981 on Wage Protection, Regulation of the Minister of Manpower No. 8 Per-04 / Men / 1989 on the Terms of Night Work and Procedures of Hiring Women Workers at Night, and Decree of the Minister of Manpower and Transmigration No. Kep. 224 / Men / 2003 on Obligations of Employers Employing Female Workers between 23:00 to 07.00. The rights of female workers to include: protection of working hours, protection during menstruation, protection during pregnancy and childbirth, including when female workers experience miscarriage (maternity leave and delivery), provision of breastfeeding sites (breastfeeding rights and / or milking), work competence rights, as well as medical rights during pregnancy and post-natal period. The rights guaranteed are in line with the international conventions regulating the rights of women workers required by the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) which has been ratified by Law Number 7 of 1984 and several other relevant conventions. Exercising feminism perspective, this study concludes that not all women workers' rights can be met, whether caused by internal factors or external factors. Internal factors contributed within the women workers themselves. Their lack of knowledge and understanding about their own rights. Whereas, influencing external factors are the existence of patriarchal culture, the marginalization in work, the stereotype of women, and lack of socialization.Hak pekerja perempuan telah dijamin dalam konstitusi, undang-undang, dan beberapa peraturan pelaksananya. Dalam konstitusi, persamaan hak perempuan untuk bekerja dan mendapat perlakuan yang layak terdapat dalam Pasal 27 dan Pasal 33. Beberapa peraturan perundang-undangan yang mengatur hak pekerja perempuan antara lain: Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, Undang-Undang Nomor 8 Tahun 1981 tentang Pelindungan Upah, Peraturan Menteri Tenaga Kerja Nomor 8 Per-04/Men/1989 tentang Syarat-syarat Kerja Malam dan Tata Cara Mempekerjakan Pekerja Perempuan pada Malam Hari, Keputusan Menteri Tenaga Kerja dan Transmigrasi Nomor Kep. 224/Men/2003 tentang Kewajiban Pengusaha yang Mempekerjakan Pekerja/Buruh Perempuan antara pukul 23.00 sampai dengan pukul 07.00. Hak pekerja perempuan tersebut antara lain: pelindungan jam kerja, pelindungan dalam masa haid (cuti haid), pelindungan selama hamil dan melahirkan, termasuk ketika pekerja perempuan mengalami keguguran (cuti hamil dan melahirkan), pemberian lokasi menyusui (hak menyusui dan/atau memerah ASI), hak kompetensi kerja, hak pemeriksaan selama masa kehamilan dan pasca-melahirkan. Jaminan hak tersebut sejalan dengan konvensi internasional yang mengatur tentang hak pekerja perempuan yang terdapat dalam Convention on the Elimination of All Forms of Discrimination Againts Women (CEDAW) yang telah diratifikasi dengan Undang-Undang Nomor 7 Tahun 1984 dan beberapa konvensi terkait lainnya. Dengan perspektif feminisme, studi ini menyimpulkan bahwa sampai saat ini belum semua hak pekerja perempuan tersebut dapat dipenuhi, baik yang disebabkan oleh faktor internal maupun faktor eksternal. Faktor internal tampak pada masih rendahnya pengetahuan dan pemahaman pekerja perempuan mengenai hak yang dimiliknya. Sementara faktor eksternal tampak pada: adanya budaya patriarki, marginalisasi dalam pekerjaan, adanya stereotype kepada perempuan, dan kurangnya sosialisasi.